Rapid poxvirus engineering using CRISPR/Cas9 as a selection tool - Gowripalan, Anjali (Commun Biol, 2020)
In standard uses of CRISPR/Cas9 technology, the cutting of genomes and their efficient repair are considered to go hand-in-hand to achieve desired genetic changes. This includes the current approach for engineering genomes of large dsDNA viruses. However, for poxviruses we show that Cas9-guide RNA complexes cut viral genomes soon after their entry into cells, but repair of these breaks is inefficient. As a result, Cas9 targeting makes only modest, if any, improvements to basal rates of homologous recombination between repair constructs and poxvirus genomes. Instead, Cas9 cleavage leads to inhibition of poxvirus DNA replication thereby suppressing virus spread in culture. This unexpected outcome allows Cas9 to be used as a powerful tool for selecting conventionally generated poxvirus recombinants, which are otherwise impossible to separate from a large background of parental virus without the use of marker genes. This application of CRISPR/Cas9 greatly speeds up the generation of poxvirus-based vaccines, making this platform considerably more attractive in the context of personalised cancer vaccines and emerging disease outbreaks.